Reliability Analysis And Optimization Of Micro Hydro Electric Power With Solar Pv And Diesel Generator Supply System: - Negassa, Muleta (My University, 2016)
Nowadays, energy is one of the most important factors needed in our world. However, some resources to obtain useful energy results are still impracticable because of the exploration cost or pollution generated using these resources, etc. The energy from flowing water and sun is the most readily available, renewable and clean source of electricity. Most of the people in Ethiopia (around 81 % of the population) live in rural areas where energy access is almost negligible. A possible reason is that these areas are far away from the national grid. Micro power electric generation is one of the most valuable answers to the question of how to offer to isolated rural communities to improve the quality of life. The aim of this thesis is to analyze the viability and optimization of a MHP for rural electrification at Fantale micro hydro project sites with solar energy using HOMER software. For this purpose the necessary data have been collected and analyzed with respect to anticipated load demand of Inkule village, then after by running the software, the simulation results for different option of power supply systems were recorded and arranged according to their net present cost (NPC). During this thesis work five different cases were taken for investigation and optimized as per the standard values generated by the software. Therefore the most economical scenario for the selected site is using 7kw hydropower , 5kw Solar PV,5kW Diesel Generator,8 Trojan L16p Battery and 6KW Convertor to supply the village loads.
Case Study On Awash River Fantale Project